Hubungan Kenaikan Berat Badan, Siklus Menstruasi dan Emosional dengan Penggunaan Suntik KB 3 Bulan di BPM Lia Amelia - Lia Amelia (Indonesia Journal of Midwifery Sciences, 2023)
Introduction: Contraceptives that are mostly chosen by acceptors in Indonesia are injectable contraceptives as much as 61.4%, but injectable contraceptives have an impact that can cause weight gain, menstrual cycle disorders and emotional disturbances. Acceptors said that injectable contraception felt more practical in the family planning process. Objectives: The purpose of the study was to determine the relationship between weight gain, menstrual cycle disorders and emotional disturbances with the use of 3 month injectable contraceptives. Method: This type of research is quantitative, analytical research design with cross-sectional approach. The population and sample in this study were all family planning acceptors as many as 55 respondents in total sampling. This research was conducted in May 2022. Data collection was done using a questionnaire sheet. Analysis of univariate and bivariate t-test data (t-test). Result: The results showed that most users of 3-month contraceptive injections experienced weight gain of as much as 65.5%, experienced menstrual cycle disorders of as much as 80.0%, and experienced emotional changes of as much as 52.7%. There is a significant relationship between weight gain and the use of 3-month contraceptive injections with p-values of 0.000 and or 186,667. There is a significant relationship between the menstrual cycle and the use of 3-month contraceptive injections with p-values of 0.001 and or 10.370 and there is a significant relationship between emotionality and the use of 3month birth control injections with p-values of 0.000 and OR 30,769. Conclusion: The most dominant side effects of using 3-month injectable contraceptives are weight gain and emotional disturbances.